ENGLISH AS A MEASUREMENT STANDARD IN THE NATIONAL EXAMINATION: SOME GRASSROOTSÃ¢â¬â¢ VOICE - Gunadi Harry Sulistyo (TEFLIN Journal: A publication on the teaching and learning of English, 2009)
Abstract: The National Examinations, including English as one component, have always implored controversies. And the government has still been determined in its commitment to execute the national examinations backed up with several accompanying arguments as an attempt to Ã¢â¬Ësmarten the life of the nationÃ¢â¬â¢. This has not, however, likely been well understood by all parties with a view to gaining communal supports from all. A small survey was conducted to analyze English teachersÃ¢â¬â¢ point of view, as frontline agents in the field, concerning issues related with the national examinations. It turns out that in spite of their positive viewpoint in the role of tests, when challenged to accepting responsibility in the context of classroom-based assessment as a part of their autonomous roles, they demonstrate an impression of disinclination.